Transformation of Resource Allocation Processes Based on Digital Technologies - Fedorovna, Suhodoeva Lyudmila; Alekseevna, Nemova Olga; Vladimirovna, Khizhnaya Anna; Valentinovna, Krylova Tatiana; Maltseva, Svetlana Mihailovna; Vladimirovna, Svadbina Tatiana (International Journal of Criminology and Sociology, 2022)
The article seeks to reveal the features of the transformation of the processes of resource provision of enterprises. In fact, a mechanism for providing resources based on digital technologies for the implementation of enterprise development programs has been developed. New approaches to the interaction of enterprises for creating digital models of development process management are formulated. A system of interaction between enterprises in the digital economy is proposed, which makes it possible to make decisions when allocating resources effectively. Among the main problems identified is the low efficiency of the methodological mechanism for resource allocation. Based on the outcomes, it can be concluded that the creation of digital technology is becoming one of the main advantages of the mutual linking of sources of the resource base at all levels of management.